The role of tax optimization in market power establishment in the digital service industry - Wimmer, Alberto (2021)
The primary objective of the thesis is to provide a conceptual correlation between the establishment of Market Power in the Digital Service Industry and Tax Optimization practices involving intangible assets. The first part of the thesis outlines a broad overview of the current tax havens, the implemented practices, and an outlook of the potential indicators to be addressed. Moreover, it discusses the impact of Tax Optimization on a firm’s performance and thus sets the scene for analyzing the drivers of Market Power. Within the Digital Service Industry, it is outlined that Market Power is primarily achieved through feedback loops and network effects, which, in turn, are reasoned by a larger financial leverage, more skillful human capital and the implementation of intellectual property. It is furthermore shown that for digital business models, governed by feedback loops and network effects, traditional measurements for Market Power are inapplicable. Thus, respective frameworks are analyzed accordingly. The findings are applied onto the case study of Alphabet Inc., which was chosen for its arguably paramount Market Power and role in Tax Optimization. The key takeaways of the thesis are shown on the SCPR framework. It is reasoned that through Tax Optimization, organizations are given a larger financial leverage allowing them to extend R&D and M&A activities, as well as to hire more skillful human capital. These outcomes, respectively, foster the development of the organizations business model in the creation of further feedback loops and network effects, thus extending their Market Power.